APPLICATION OF WSOLA & GWSOLA ALGORITHMS FOR PACKET LOSS CONCEALMENT - Ms. More Vrushali Shivaji; Assi.Prof. Shridevi A.Talle; Mr. Sajid Shaikh (International Journal of Innovations in Engineering Research and Technology, 2021)
This papergives an overlook of time scale algorithms used for packet loss concealment.The time scale modification (TSM) approach can be used to overcome the quality degradation at the packet loss regions.The Overlap and add (OLA) algorithm does not consider what are the content of the input signal rather it just overlap and add the signal.To avoid time discontinuitiessynchronous overlap and add (SOLA) algorithm is introduced.The disadvantage of SOLA is that it does not maintain maximum local similarity. To overcome this problem WSOLA technique is used. This technique good quality output sound than other time scale modification algorithms.Gain control into the standard WSOLA technique which could adjust the level of the audio segments for overlap and add in order to maintain the audio signal level consistent. GWSOLA algorithm can be applied in the packet loss concealment of real time voice communications